Exploring Creative Entrepreneurs’ IEO: Extraversion, Neuroticism and Creativity - Gao, Yang; Zhang, Dixuan; Ma, Hongjia; Du, Xiaomin (Frontiers in Psychology, 2020)
In the creative industry, entrepreneurs’ creativity is the source of entrepreneurial activities. Meanwhile, the key to the success of entrepreneurship lies in the strategic tendency of leaders, referred to the individual entrepreneurial orientation (IEO). This paper is aimed to explain the process from creativity to IEO and reveal the psychological process of entrepreneurs' creativity. We proposed an integrated model of “individuality-creativity-IEO” by drawing on the theories of big five personality and entrepreneurship. Using a sample of 202 creative entrepreneurs from China, the research found that entrepreneurs’ creativity has a positive impact on IEO, and the individuality of neuroticism and extraversion exhibited a negative U-shaped relationship with creativity. Finally, implications for both theory and practice were presented.